Pengujian Berbagai Jenis Pupuk Kandang Dan Dosis Pupuk Majemuk Npk 17:17:17 Terhadap Pertumbuhan Dan Produksi Tanaman Kacang Hijau (Vigna Radiata L.) - Trika Darma; Aidi Daslin Sagala; Hadriman Khair (Mahesa Research Center, 2022)
This study aims to determine the testing of various types of manure and the dose of compound fertilizer NPK 17:17:17 on the growth and production of green beans (Vigna radiata L.). This study used a split plot design (RPT) with 2 factors. Parameters measured were plant height, number of primary branches, flowering age, number of filled pods per plant, number of empty pods per plant, number of seeds per pod, seed yield per plant, seed yield per plot, weight of 100 seeds. Observational data were analyzed using analysis of variance (ANOVA) and continued with Duncan's mean difference test (DMRT). The results showed that the treatment of chicken manure gave the best effect on plant height, number of primary branches and weight of 100 mung bean seeds. The treatment of various doses of NPK 17:17:17 compound fertilizer did not affect all the observed parameters. There was no interaction between the type of manure and the dose of compound fertilizer NPK 17:17:17 on all observation parameters.